Smooth mode transfer in AC microgrids during unintentional islanding. (October 2017) - Issa, Walid; El Khateb, Ahmad; Anani, Nader; Abusara, Mohammad
Abstract: Microgrid coordinated controllers are designed so as to optimize the utilization of energy available in existing energy storage system (ESS) as well as the energy being generated from prevailing renewable energy sources (RES). If there is a surplus in the generated renewable energy, it will be used to charge the ESS if their capacity permits, otherwise, the surplus energy is curtailed. However, during a grid loss, i.e. during unintentional islanding, the surplus energy can lead to an increase in the DC link voltages feeding the DC-AC inverters, which may subsequently trip them off. Clearly, this has an adverse effect on the reliability of the microgrid. In this paper, a new strategy of microgrid control is proposed for enhancing the microgrid reliability by protecting it against unintentional islanding instability. In this strategy, the DC link voltage is used as a feedback parameter in the droop control loop. This bounds the DC link voltages and consequently leads to reliable operation. The validity of the proposed control scheme was verified by software simulations using MATLAB/Simulink.